x>0 y>0 化简4x^(√2/2)*3x^-(√2/2) * (-y√3)^-(√3/3)
2个回答
4x^(√2/2)* 3x^-(√2/2) * (-y^√3)^-(√3/3)
=-12x^(√2/2-√2/2)*y^(-√3*√3/3)
=-12x^0*y^(-1)
=-12/y
相关问题
已知x>0,y>0,化简:4x^√2/2·3x^-√2/2·(-y^√3)^-√3/3
已知x>0,y<0,化简:/3x-2y/-/3y-2x/
(2x+y)^2-4x-2y-3=0怎么化简
化简求值(0.2x^3-x^2y-xy^2)-(xy^2-x^2y-0.5x^3)+0.3x^3其中x=-3y=-2
化简函数 (x^2+y^2+1)^3 -x^2y^3=0
已知:|x+3|+(2x+y)2=0,先化简:[3/4]x2-(3y-[1/4]x2)+y,再求值.
怎么化简-2(x-3y) 3(2x-y)-4(2x 3y)?
化简根号x^2/2y^3(x>0)
(2X-3Y+4)(-2X-3Y-4)化简
化简求值[(x+0.5y)^2+(x-0.5y)^2](2x^2-0.5y^2),其中x=-3,y=4.